ANALISIS PENGARUH SELF ACTUALIZATION DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL INTERVENING (Studi Pada PT. Kereta Api Indonesia (Persero) Daop IV Semarang) - Jayanti, Aulia Fitri; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2015)
The company has the capital resources, one of which employees. The existence of the employees is very important to the survival of a company. Therefore, a company's success is measured by the performance of employees. High employee performance makes the success of the company is also getting higher. Many steps can be done in improving the performance of employees. One of them is to do self-actualization and creating job satisfaction of employees. With the creation of self-actualization and job satisfaction, can increase Organizational Citizenship Behavior (OCB) among employees, which then affects their performance. The aim of this study is to describe and analyze the influence of self-actualization and job satisfaction on employee performance with Organizational Citizenship Behavior (OCB) as an intervening variable.This research was conducted by distributing questionnaires to a sample of 70 permanent employees of PT. Kereta Api Indonesia (Persero) Daop IV Semarang using random sampling techniques, with the draw. Data analysis method used is multiple linear regression analysis. Mechanical testing data used this study include the path analysis and Sobel test to test the effect of mediation.The results showed that self-actualization positive and significant influence to Organizational Citizenship Behavior (OCB) and employee performance, job satisfaction and significant positive effect on Organizational Citizenship Behavior (OCB) and employee performance, and Organizational Citizenship Behavior (OCB) positive and significant influence on employee performance. Additionally, Organizational Citizenship Behavior (OCB) capable mediating the relationship between self-actualization and job satisfaction on employee performance.